Effects of varying levels of lemon juice on the palatability and shelf stability of queso-blanco cheese (2008)
The effects of varying concentration of Lemon juice on the preparation of Queso Blanco Cheese (QBC) and on its palatability and microbiological composition was investigated. The QBC was manufactured from raw and morning milk adjusted to 3.0% fat. Completely randomized design was used for the study. Varying levels of lemon juice (2.5%, 3.0% and 3.5%) were used per treatment. Organoleptic evaluation of prepared cheese was carried out using a five point hedonic scale for quality traits for the colour, taste, smell, texture and overall acceptability of the cheese revealed that QBC made with 2.5% lemon juice was rated highest (4.9±0.32) for overall acceptability and for all parameters tested for on day one. Cheese prepared with 3.5% lemon juice recorded the lowest plate count for all the days. In conclusion Cheese prepared with 2.5% lemon juice was more acceptable, however, the plate count was highest for all the days for this treatment.